La comunidad piamontesa de Argentina - Giolitto, Marco (Verbum – Analecta Neolatina, 2008)
Like many other Romance languages, Piedmontese (a Gallo-Italian dialect from northern Italy) is spoken in Argentina. A wave of immigration touched Argentina between 1875 and 1914, between the depression of the last decades of the 19th century and World War I. The dominant language of the region, "Pampa Gringa", or the dominant foreign language of the area, was, until the 1950s, Piedmontese. It was only after the 1950s that Spanish took hold. Today it is practically the only spoken language, except in a few areas where the older generation continues to speak Piedmontese. The present paper is the result of a long investigation into this community, which included over 300 interviews with the descendants of the original immigrants. The paper has two objectives: to reconstruct the linguistic customs of the Piedmontese from the time of their arrival in Argentina up to today, and to collect the impressions and attitudes that their descendants have towards Piedmontese, as well as their relation to Castilian Spanish.